Modes Of Learning to Read as The Basic Processes in Language Learning (Eurasian Journal of Learning and Academic Teaching, 2021)
This article discusses the modes of learning to read both the basic processes in language learning. It says that at the initial stage of training is necessary to teach the slow reading of a literary text, that is, the child must consider during the reading of the meaning of each word, and be able to ask questions and find the same to them here the answers in the text; be able to reflect and empathize, and to do an analysis of reading. In - the second you need to understand that we teach a child to read is not for us adults, and for themselves. So, it is necessary to learn to understand other people's thoughts.